Assessment of the mainshock-aftershock collapse vulnerability of RC structures considering the infills in-plane and out-of-plane behaviour. (2017) - Furtado, André; Rodrigues, Hugo; Arêde, António; Varum, Humberto
Abstract: One major challenge of earthquake risk mitigation is the assessment of existing buildings not designed with modern codes and the development of effective strengthening techniques. Particular attention should be given to reinforced concrete (RC) frame structures with infill masonry (IM) panels, as proved by their poor performance in recent earthquakes. From surveys on damaged and collapsed RC buildings, many buildings suffered severe damage or collapse due to the IM panels presence. It is observed that in-plane (IP) behaviour of IM can prevent the development of out-of-plane (OOP) strength mechanisms by arching effect. By contrast, in most cases the major damages were found in non-structural elements, particularly in clay IM, including diagonal cracking, OOP collapse or detachment of surrounding RC frames (the latter taking place in early earthquake instants) due to absence of or deficient connection to that frames. In a seismically active region, structures are subjected to multiple earthquakes, due to mainshock–aftershock phenomena or other sequences, leaving no time for rehabilitation of the buildings or rescue of the injured people between the events. This research pretends to assess the mainshock-aftershocks effects on an eight storey RC building. For this, different numerical models (considering different IM walls modelling strategies) were subjected to several non-linear dynamic analyses. The structure damage level was evaluated for different intensity levels of the aftershock-mainshock by the comparison between the maximum inter-storey drifts with drift limits suggested by international codes.